Journalism ethics in Malaysia entertainment industry / Nurul Ayuni Mohd Nuzulrudin…[et.al] - Mohd Nuzulrudin, Nurul Ayuni; Ahmad Azwadi, Nur Yashira Yasmin; Abdul Aziz, Nur Wan Izyan Hani; Suhaimi, Sakinah; Mathiew, Valenditro (Faculty of Communication and Media Studies, 2016)
The title of this research paper is Journalism Ethics in Malaysia Entertainment Industry. This research paper is to find out the journalism ethics that have been practiced all this while by all the entertainment journalists and reporters in Malaysia. It shows how important journalism ethics is in writing a news. Journalism is a form of writing that tells people what already happened but they are not aware of it (Niles, 2015). While an entertainment journalists are the person who cover all the news and events within the industries of film, television, music, live events, video games, and others (Entertainment Journalist, 2016).